2008
DOI: 10.1177/003335490812300313
|View full text |Cite
|
Sign up to set email alerts
|

Companion Animals as Sentinels for Community Exposure to Industrial Chemicals: The Fairburn, GA, Propyl Mercaptan Case Study

Abstract: SYNOPSISObjectives. This study utilized the electronic medical records of six veterinary hospitals (operated by Banfield, The Pet Hospital ® ) in the vicinity of Fairburn, Georgia, to assess the health of dogs and cats following the unintentional release of propyl mercaptan from a waste-processing facility.Methods. Standardized electronic medical records were used to define clinical syndromes (eye inflammation, gastrointestinal, respiratory, fever, general weakness/change in mental state) in dogs and cats. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Banfield EPR data were linked with Antech Diagnostics electronic laboratory reports from over 18,000 private veterinary practices [ 117 ]. Resultant publications on dog health have covered vaccine safety [ 19 , 107 , 118 , 119 ], tick infestation [ 108 ] and toxic exposure [ 115 ]. However, NCASP surveillance was limited by confidentiality issues, delayed dissemination of results and difficulties in managing such large volumes of data [ 117 ].…”
Section: Reviewmentioning
confidence: 99%
“…Banfield EPR data were linked with Antech Diagnostics electronic laboratory reports from over 18,000 private veterinary practices [ 117 ]. Resultant publications on dog health have covered vaccine safety [ 19 , 107 , 118 , 119 ], tick infestation [ 108 ] and toxic exposure [ 115 ]. However, NCASP surveillance was limited by confidentiality issues, delayed dissemination of results and difficulties in managing such large volumes of data [ 117 ].…”
Section: Reviewmentioning
confidence: 99%
“…The pets, particularly the dogs and cats, are of particular interest, given that they share the habitat with humans and they respond to toxic assaults similar to their owners (Backer et al 2001). Thus, many studies have been designed to reveal the shared exposure of humans and dog/cats to different environmental toxicants of anthropogenic origin, such as asbestos (Glickman et al 1983;Backer et al 2001), tobacco smoke (Ka et al 2014), industrial pollutants (Maciejewski et al 2008;Bischoff et al 2010), pesticides (Knapp et al 2013) or smog (Heyder & Takenaka 1996;Calderon-Garciduenas et al 2001), among others. Most of these studies have found associations between exposure and elevation of the selected biomarkers, as well as correlations between the incidence of diseases related to exposure to such pollutants between pets and humans.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum is an essential trace element for nearly all organisms [ 100 , 101 ]. It is found in human tissues in a range from 0.001 to 0.4 mg/kg of tissue, with the lowest values in the blood and the highest in the kidneys and liver [ 73 , 102 ]. The average value in the soft tissues is <0.075 mg/kg and, in the skeleton, <0.48 mg/kg [ 103 ].…”
Section: Discussionmentioning
confidence: 99%